(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
Water that is clean and hygienic must be available for drinking. Most of the water that is currently available needs to be cleaned. When water is contaminated, it may be required to recycle it. Water must be treated to eliminate impurities and standardize variables like turbidity and pH. Many of the treatment facilities employ any organic coagulants for the treatment, like alum, ferrous sulphate, etc.The usage of plant-based coagulants was developed since these coagulants are hazardous to living things.The utilization of biological plant materials as coagulants, such as agricultural waste, Chitosan, Moringa oliefera, maize seed, cactus plant, etc., has been thoroughly researched. In this project, studies are carried out to determine the turbidity removal efficiency utilizing locally accessible moringa oliefera. The outcomes are encouraging because the optimal dosage is 200 mg/l with an 88.9% clearance efficiency in dry form.